ADMITS: Architecting Distributed Monitoring and Analytics in IoT-based Disaster Scenarios - Pasquini, Rafael; Miani, Rodrigo S.; Coelho, Paulo R.; V. Neto, Augusto; Hidalgo, Nicolás; Gutiérrez, Martín; Rosas, Erika; Baliosian, Javier; Grampín, Eduardo (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2020)
The ADMITS project aims to develop algorithms, protocols and architectures to enable a distributed computing environment to provide support for monitoring, failure detection, and analytics in IoT disaster scenarios. We face a context where, every year, millions of people are affected by natural and man-made disasters, whereby governments all around the world spend huge amounts of resources on preparation, immediate response, and reconstruction. Recently, the Internet of Things (IoT) paradigm has been extensively used for efficiently managing disaster scenarios, such as volcanic disasters, floods, forest fire, land- slides, earthquakes, urban disasters, industrial and terrorists attacks, and so on. However, in a disaster scenario the communication/processing infrastructure and the devices themselves may fail, producing either temporary or permanent network partitions and loss of information. Moreover, it is expected that in the years to come, IoT will generate large amounts of data, making processing and analysis challenging in time-critical applications. Considering such challenges, ADMITS targets the development of a architecture in which IoT, Fog, and Cloud computing technologies participate to provide required capabilities for IoT data analytics, real-time stream processing, and failure monitoring for environments potentially subject to disasters. In this positional paper, we discuss the motivation, objectives, architecture, research challenges (and how to overcome them) and initial efforts for the ADMITS project.